The Effect of Educational Background, Working Period, and Training on Employee Performance - Syukur, Abdul; Perkasa, Didin Hikmah (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This study aims to determine the effect of educational background, years of service and training on the performance of Engineering employees at Summarecon Mall Kelapa Gading, a subsidiary of PT. Summarecon Agung Tbk. This research is a survey research using a questionnaire. The sampling technique used in this study is a saturated sample. Saturated sample is a sampling technique in which all members of the population are used as research samples. The validity test used in this study is Product Moment, while the reliability test uses Cronbach's Alpha. Test the hypothesis using the F test, t test and test the coefficient of determination.It can be seen that the results of obtaining Fcount in column F in the Anova table are 25.945 with a significance level = 0.000 greater than the Ftable value of 8.590 with an error rate of α = 5%, or in other words Fcount > Ftable (25.945 > 8.590). Based on the criteria for testing the hypothesis. if Fcount > Ftable and its significance level (0.000 <0.05), indicates that the influence of the independent variables educational background (X1), years of service (X2) and training (X1) simultaneously is significant or has an effect on the dependent variable (employee performance) . If the value of F count> F table, it means that the Independent variable (X) Simultaneously influences the dependent variable (Y).